Application Of Data Mining To Analyze Sales Data At Pebi Stores Using Apriori MethodApplication Of Data Mining To Analyze Sales Data At Pebi Stores Using Apriori Method - Keken Ardiansyah; Maryaningsih Maryaningsih; Reno Supardi (Jurnal Komputer, Informasi dan Teknologi, 2023)
Toko Pebi is one of the business places that sells various kinds of household items such as plastic chairs, spring bads, sofa bads, dining tables, and others that can be purchased by consumers. The purpose of this research is to provide information on which items are in greatest demand and which items are less in demand through the a priori algorithm. The application of data mining to analyze sales data at Toko Pebi is used to provide information on the results of the analysis of sales data at Toko Pebi every month which can be used as a parameter in managing the inventory of goods at Toko Pebi, besides that it can provide information on the items that sell the most at Toko Pebi. In analyzing the sales data, the Apriori Method has been applied, so that the stages of the final results of the analysis go through the stages of the Apriori Method by meeting the minimum support and minimum confidence that have been previously determined. Based on the results of tests that have been carried out on a sample of data for December 2022 as many as 30 transactions, it is found that the sales of goods that are most in demand by the community are dining chairs and dining tables that meet the minimum support of 20% and confidence of 50%.